A novel Y160C mutation of Keratin 10 gene in a Chinese male infant with epidermolytic hyperkeratosis - Zhao, Chenyu; Li, Yonggui; Shi, Gaoxing; Shi, Xiaoliu; Zhang, Guiying (The Turkish Journal of Pediatrics, 2018)
Epidermolytic hyperkeratosis (EHK) is a rare genodermatosis whose prevalence is less than 1 in 100,000. Mutations in either the keratin 1 or keratin 10 genes lead to EHK characterized by congenital erythema and epidermal blisters at birth, followed by hyperkeratotic skin lesions with age. We here report a 1-and-a-half-year-old male infant with EHK caused by a novel mutation, c.479A > G, g.489A > G, p. Y160C, of the keratin 10 gene. Mutation at this position has been reported previously, but the type of amino acid change was different. These results expand the database of keratin 10 gene mutations.